SMOC - Método Abierto de Coordinación de Prevalet Informe de progreso conjunto de las regiones sobre la aplicación de las estrategias europeas de aprendizaje a lo largo de toda la vida - Hacia una gobernanza multinivel - - Federighi, Paolo; Torlone, Francesca (Proceedings e report, 2011)
Seven European Regional Governments, together with Earlall and universities and research centres, have undertaken to refine a first draft of a Joint Progress Report of Regions on Implementation of European Lifelong Learning Strategies in the perspective of the Europe 2020 Strategy. The purpose of this exercise is to demonstrate the usefulness and need to make an instrument available to European Regional Governments that helps to understand and evaluate the educational conditions of the regional population when compared with other regions. The Report shows how, over the decade, all the Regional Governments have undertaken to adapt training systems to the demographic dynamics characterised by the general ageing of the population and by migratory phenomena. Simultaneously the Report also shows the need for urgent improvements in some fields where the impact of policies is still too modest and where the risk of stagnation must be dealt with (for example, lifelong learning policies and NEET reduction).